Phyto-pharmacological review of Portulaca quadrifida Linn. - Das, Mrinmay; D., Ashok Kumar (Journal of Applied Pharmaceutical Research, 2013)
Portulaca quadrifida Linn. (Family: Portuleacea), commonly known as “Chicken Weed”, a traditional medicinal plant has been used in the Ayurvedic system of medicine for centuries, valued for its benefits in the management of urinary and inflammatory disorders. The juice of leaves is applied to abscesses and decoction is given in dysentery. The decoction of the plant can act as anthelminthic and used in the treatment of stomach complaints and gonorrhoea. Portulaca quadrifida has been reported to possess antifungal activity. The effect of ethanolic extract of Portulaca quadrifida on central and peripheral nervous system were studied by using spontaneous motor activity, in vivo muscle relaxant activity (Grip strength) and anticonvulsant activity and it is also found to have good effect on central nervous system. In this review, we have explored the Phyto-pharmacological properties of the Portulaca quadrifida plant and compiled its vast pharmacological applications to comprehend and synthesize the subject of its potential image of multipurpose medicinal agents.